Measuring inclusive education - Loreman, Tim; Forlin, Chris (International perspectives on inclusive education ;, 2014)
In the first section, broad issues associated with assessment for, of, and in learning in inclusive classrooms; measuring the implementation of inclusive policy; identifying and removing barriers to inclusion; resourcing and financing; and, evaluating effective teacher preparation for inclusion provide the structure for discussion. The second section commences with a current and in-depth review of the literature on the development of international indicators for measuring inclusive education. Examples of some of the models presently employed to frame an evaluation of inclusive practice are studied. These provide illustrations of effective measurement strategies to evaluate inclusive educational practice at all levels of administration, from governments to classrooms, and ways to recognize the positive outcomes attained by all involved.